Novel low-voltage RF-MEMS switch: design and simulation - Ma, Li Ya; Soin, Norhayati; Nordin, Anis Nurashikin (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper presents a novel design of a low-voltage radio frequency (RF) micro-electromechanical system (MEMS) switch with its electro-mechanical and microwave characteristics’ simulation, as well as its virtual fabrication process. The RF-MEMS switch employs a shunt capacitive structure. There are eight beams supporting a rectangular membrane to suspend over a coplanar waveguide (CPW) transmission line. The outer four crab-leg beams are used to bypass the signal line to the ground by the coupling capacitance and via when switch is actuated; and the inner four serpentine beams are used to supply the DC actuation voltage to the membrane. The developed RF-MEMS switch has a very low pull-in voltage of 3.53V; and the maximum von Mises stress under actuated condition is 13.1808MPa. The capacitance ratio of the switch is 218.5, with switch-on capacitance of 68fF. The switch’s microwave characteristics are obtained by AWR Design Environment 10® simulation; its insertion loss and isolation is -1.7532dB and -18.394dB respectively at 20GHz; and at frequency of 60GHz, the insertion loss is -7.2499dB and isolation is -27.293dB. A simple low-cost three-mask process with photoresist (PR-S1800) as sacrifice layer to release the membrane is proposed in this design; and a virtual fabricated device is simulated using IntelliFab v8.7® software.